Leslibetaeus coibita, n. gen., n. sp., a new alpheid shrimp from the Pacific coast of Panama (Crustacea: Decapoda) - Anker, Arthur; Poddoubtchenko, Denis; Wehrtmann, Ingo S. (Zootaxa, 2006)
A new alpheid shrimp, Leslibetaeus coibita, n. gen., n. sp., is described on the basis of two specimens extracted from crevices in a shale rock on the rocky intertidal shore in the Isla Coiba National Park, Pacific coast of Panama. Leslibetaeus is characterized by absence of rostrum and orbital teeth; eyes being only partially covered by carapace; sixth abdominal somite without articulated plate; first segment of the antennular peduncle without tooth on ventromesial carina; short scaphocerite; tip of third maxilliped with stout spines; and strap-like epipods present on third maxilliped and first to fifth pereiopod; stout symmetrical chelipeds, with carpus distally strongly lobed and bearing two rows of setae mesially, and chela without snapping mechanism; carpus of second pereiopod five-segmented, with second segment distinctly longer than first; ischium and merus of third pereiopod unarmed. The new genus appears to be relatively basal and not closely related to any of the currently described alpheid genera. The finding of this new taxon in a relatively accessible habitat indicates a yet unexplored biological potential of the Isla Coiba National Park.